Certain difficulties felt by Anglicans in Catholic teaching considered - Newman, John Henry (Works of Cardinal Newman, 1914)
Vol. 1. Twelve lectures addressed in 1850 to the Party of the Religious movement of 1833.- Vol. 2. A letter addressed to Rev. E.B. Pusey, D.D., on occasion of his Eirenicon of 1864. Letter addressed to the Duke of Norfolk on occasion of Mr. Gladstone's expostulation of 1874.